The City and Its Ways of Life : Local Influences on Middle-Income Milieus in Nairobi - Florian Stoll (Revue Internationale de Politique de Développement)
How is it possible to study the ‘cityness’ of cities, their particular character and the locally specific actions of their residents? One crucial aspect that distinguishes cities from one another is how social phenomena are embedded in a particular city’s built environment, its economy, and particular horizons of meanings. To analyse a significant example of this embeddedness, this chapter examines Kenya’s Nairobi through the lens of social milieus in the middle-income stratum, the so-called ‘middle classes’. Moreover, the milieu concept enables the identification of social groups that share sociocultural features such as specific ways of life, professional and leisure activities, and forms of consumption and investment. The text studies which local aspects are significant for milieus in Nairobi in comparison to Mombasa and other Kenyan cities. And, using two case studies, the Christian Religious Milieu and the milieu of the Young Professionals, it illustrates how the particular city modifies these milieus. Such an approach not only allows for a better understanding of the ‘middle classes’ in African cities as comprised of different identifiable milieus, it also yields a method for analysing the local particularities of a city, whether in Africa or other parts of the world. The chapter is significant for policy and practice because it introduces with the concept of social milieus a nuanced alternative to (middle) class approaches that distinguishes lifestyles, aims in life and forms of consumption. Also, the chapter discusses, using the example of Nairobi, how milieus are bound to specific structures of a city and might offer—from the perspective of basic research—suggestions for practical use.